Fulfillment of Gender Needs of Students at School - Tiyas Nur Haryani; Ismi Dwi Astuti Nurhaeni; Azyani Zulfatindayu; Muchtar Hadi; Priyanto Susiloadi (International Islamic Schools Alliance, 2016)
Education is an important factor in building the country. Educating a child means building the nation. Nowadays, education takes place more in the secondary scope than in family environment. Schools play an important role in educating children in cognitive, affective, and psychomotor aspects. In Indonesia, the case of sexual abuse to children increases currently. The cases of sexual abuse result from unequal gender relations. Gender-responsive schools develop in line with the policy of gender mainstreaming in Indonesia. The school environment needs to meet the practical and strategic gender needs of its students. The results of this research described the students’ needs for gender in the school environment. Gender needs are expected to support zero sexual abuse of children. The research was conducted in the Senior High School in Sragen, Central Java Province, Indonesia representing Soloraya area. Primary data was collected through questionnaires with random sample. Data was presented in tables, charts and descriptions. The results showed the fulfillment of practical and strategic gender needs has not been optimal in schools in Sragen regency. The number of sexual abuse against children is still high due to the lack of monitoring. The results of this study recommended the collaboration to be strengthened in order to reduce gender-based violence and the development of institutional gender mainstreaming at schools.